How Robust are Money Demand Estimations? A Meta-Analytic Approach - Markus Knell; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2003)
In this paper we perform a meta-analysis of empirical money demand studies involving almost 500 individual money demand estimations. We analyze whether the wide variety of results can be explained by characteristics of the studies, different macroeconomic environments or the imprecision of individual estimates. We find that estimates for the income elasticity of money are systematically related to various study characteristics (e.g., broadness of the monetary aggregate, inclusion of financial innovation and wealth, etc). Also, the macroeconomic environment (inflation, nominal and real uncertainties) seems to play a role. Nevertheless, a substantial part of the variability remains unexplained. Our findings thus raise some doubts about the robustness and reliability of money demand estimations.
Keywords: E41; E52; 330; Money Demand; Meta Analysis; Empirical Methods